Sharia-Based Waste Circularomics as A Model for Economic Development in Indonesia - Insawan, Husain; Anhusadar, Laode; Alwahidin, Alwahidin; Insawan Putri, Azzahrah (El-Usrah: Jurnal Hukum Keluarga, 2026)
This study investigates the implementation of a syariah-based circular economy model in waste management within Kendari and Bau-bau, Indonesia. The research addresses the gap in existing literature by exploring the application of syariah principles in creating a sustainable waste management system. The research employs a qualitative approach, utilizing observations, in-depth interviews with stakeholders, and focused group discussions to gather comprehensive data. The findings reveal significant achievements in integrating syariah principles, such as al-amanah (responsibility), al-iqtishadiyah (efficiency), and al-'adalah (justice), into the waste management systems. Technological innovations, such as biogas conversion at TPA Puwatu, have shown success in addressing waste issues and providing economic benefits. Additionally, educational and community empowerment programs have effectively increased public participation in sustainable waste management practices. The study concludes that the syariah-based circular economy model is effective in creating a sustainable and ethical waste management system, with potential for broader application in other regions. The research highlights the importance of integrating religious principles with modern environmental practices to achieve holistic sustainability.